IMPLEMENTACIÓN DE LA CONTABILIDAD EN LA DISTRIBUIDORA “DISFARBE” DE LA CIUDAD DE LOJA. PERÍODO DEL 1 DE SEPTIEMBRE AL 31 DE DICIEMBRE DEL 2017 - Iñiguez Granda, Carlos Patricio (2018)
The research work called: "IMPLEMENTATION OF ACCOUNTING IN DISTRIBUTOR DISFARBE OF THE CITY OF LOJA. PERIOD FROM SEPTEMBER 1 TO DECEMBER 31, 2017. ", consists of implementing a multiple account system, which allows to have accurate, real and timely information of the activities that are being carried out in it, able to give them a guideline to its owners, for decision making, likewise was developed in compliance with a requirement prior to obtaining the degree of Accounting and Audit Engineer, Auditing Public Accountant in accordance with the Academic Regulations in force. For the fulfillment of the objectives, a chart of accounts and account manual was prepared, which will serve for a better understanding and use of the respective accounting accounts that were adapted to the needs of the distributor, classifying them according to the nature of the each account with its respective code for better management and use of them in the accounting process. We proceeded to structure the initial inventory of the distributor registering its assets, values and obligations; classifying with the respective accounting account according to its nature. Purchase and sales assistants were designed and developed, which served to order and synthesize the purchase and sale transactions made by the distributor during the study period. This procedure facilitated the recording of the accounting entries in the Daily Book, its pass to the Mayor, Balance of Verification and preparation of Financial Statements. In addition, salaries 5 and provisions payment roles were prepared for each month that served as support for the accounting record at the time salaries were paid. Finally, this process was formulated the conclusions and recommendations to improve the situation of the distributor since it does not have a bookkeeper and an accounting system that provides timely and adequate information for which it is recommended: implement the accounting system proposed with the purpose of knowing the financial economic situation, being a necessary tool for decision making; Based on the foregoing, it is concluded that the implementation of the accounting system is of utmost importance and therefore the owner can have accurate, reliable information and especially on time to make the right decisions.